2010
DOI: 10.1152/ajpregu.00813.2009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of nitrite uptake and hemoglobin-nitrite reactions in erythrocytes: sorting out uptake mechanisms and oxygenation dependencies

Abstract: Nitrite uptake into red blood cells (RBCs) precedes its intracellular reactions with hemoglobin (Hb) that forms nitric oxide (NO) during hypoxia. We investigated the uptake of nitrite and its reactions with Hb at different oxygen saturations (So(2)), using RBCs with (carp and rabbit) and without (hagfish and lamprey) anion exchanger-1 (AE1) in the membrane, with the aim to unravel the mechanisms and oxygenation dependencies of nitrite transport. Added nitrite rapidly diffused into the RBCs until equilibrium. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…(pHRBC-pHex) (Jensen and Rohde, 2010). The lower pH inside RBCs than outside therefore predicts a ratio lower than 1, implying [ the level of SNO compounds measured with reductive chemiluminescense is ~0.05moll -1 MacAthur et al, 2007), which corresponds with the SNO concentrations in normoxic goldfish RBCs (Fig.6B).…”
Section: Basal Normoxic Values Of No Metabolitesmentioning
confidence: 90%
See 1 more Smart Citation
“…(pHRBC-pHex) (Jensen and Rohde, 2010). The lower pH inside RBCs than outside therefore predicts a ratio lower than 1, implying [ the level of SNO compounds measured with reductive chemiluminescense is ~0.05moll -1 MacAthur et al, 2007), which corresponds with the SNO concentrations in normoxic goldfish RBCs (Fig.6B).…”
Section: Basal Normoxic Values Of No Metabolitesmentioning
confidence: 90%
“…However, the literature on the ratio between nitrite concentrations in RBCs and plasma is conflicting. Some investigations report higher RBC nitrite levels than plasma nitrite levels (Bryan et al, 2004;Dejam et al, 2005) (Bryan et al, 2005;Feelisch et al, 2008;Jensen and Rohde, 2010) as observed in normoxic goldfish. Nitrite appears to be rapidly transported across the RBC membrane via both nitrous acid (HNO 2 ) diffusion and anion exchanger 1-mediated facilitated NO 2 -diffusion, which predicts that the equilibrium distribution ratio between intracellular (RBC) and extracellular (ex) nitrite is related to the proton distribution according to:…”
Section: Basal Normoxic Values Of No Metabolitesmentioning
confidence: 97%
“…In the turtle, it is possible that nitrite for erythrocyte NO generation might have originated from some of the tissues that were perfused by blood during anoxia. It is known that nitrite permeates cellular membranes and is transported into red cells and tissues upon an elevation of extracellular levels (Bryan et al, 2005;Feelisch et al, 2008;Jensen and Rohde, 2010) or exposure to reduced O 2 levels (Hansen and Jensen, 2010;Sandvik et al, 2012). Measuring nitrite in tissues other than blood in future studies will help to establish the role of nitrite as a source of NO during anoxia in turtles.…”
Section: Basal No Metabolites and Thiols In The Bloodmentioning
confidence: 99%
“…Possibly present in the fish-specific heme-containing proteins that perform the function of maintaining the balance of the activity of argininedependent nitrite (nitrate)-reductase contours nitrogen oxide cycle, determine the level of resistance of fish species to oxygen deficiency and the effectiveness of organ protection mechanisms against reperfusion injury (Cossins et al 2009). In turn, the species-specific resistance of fish to high concentrations of exogenous nitrite (Jensen 2007;Jensen and Rohde 2010) may depend on the intensity of the transport of mineral substances in the cells of the gill apparatus, the rate of accumulation of nitrite in the intracellular sector and the efficiency of hemoglobindependent resynthesis NO. In our opinion, should also be noted that the sharp surge in activity intraorganic arginine-dependent NO synthesis can cause growth intraorganic and systemic concentration of endogenous nitrite in fish.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally confirmed the possibility of using fish of exogenous nitrite as substrates in reactions resynthesis NO. However, attention is drawn to the following pattern-the authors of most-cited publications recognize that normally the content in the extracellular fluid of fish physiologically active metabolites of NO-endogenous nitrite is constant (Jensen 2007;Tripathi and Krishna 2008;Cossins et al 2009;Jensen and Rohde 2010). Taking note of the reasoned reviewed publications in the importance of the physiological role of nitrite to fish, the existence of specific mechanisms that determine their kinetics in the body, and narrow ranges of concentration in the extracellular fluid, it can be assumed that normally the level of nitrite is a physiological constant.…”
Section: Introductionmentioning
confidence: 99%